2008
DOI: 10.1063/1.2963359
|View full text |Cite
|
Sign up to set email alerts
|

The search for mechanically stable PbTe based thermoelectric materials

Abstract: The search for alternative energy sources is nowadays at the forefront of applied research. In this context, thermoelectricity for direct energy conversion from thermal to electrical energy plays an important role, in particular, for the exploitation of waste heat [G. J. Snyder and E. S. Toberer, Nat. Mater. 7, 105 (2008); M. S. Dresselhaus et al., Adv. Mater. (Weinheim, Ger.) 19, 1043 (2007)]. Materials for such applications should exhibit thermoelectric potential as well as mechanical stability. PbTe based a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 7 publications
1
62
0
1
Order By: Relevance
“…21 Gelbstein et al found that n-type PbTe is much stronger in its bending strength and more ductile than p-type PbTe. 22 They also discussed the microhardness enhancement of p-type PbTe alloys with hole concentrations higher than 5×10 18 cm -3 , 23 which agrees well with Zlatanov's experimental observation. 24 Cui et al prepared the binary alloys (PbTe) 1-x (SnTe) x over the whole composition range and found that alloys with mole fraction x ranging from 0.2 to 0.6 have the highest compression strengths (310 -330 MPa) and hardness (HV95).…”
Section: Introductionsupporting
confidence: 75%
“…21 Gelbstein et al found that n-type PbTe is much stronger in its bending strength and more ductile than p-type PbTe. 22 They also discussed the microhardness enhancement of p-type PbTe alloys with hole concentrations higher than 5×10 18 cm -3 , 23 which agrees well with Zlatanov's experimental observation. 24 Cui et al prepared the binary alloys (PbTe) 1-x (SnTe) x over the whole composition range and found that alloys with mole fraction x ranging from 0.2 to 0.6 have the highest compression strengths (310 -330 MPa) and hardness (HV95).…”
Section: Introductionsupporting
confidence: 75%
“…The first papers dedicated to the hardness determination for this compound appeared almost fifty years ago [1,2]. In single n-type PbTe bulk crystal grown by the Bridgman method the microhardness is almost a constant value of H ≈ 300 MPa for various electron concentration whereas in p-type material this value strongly increases with the hole concentration and can be as high as H ≈ 700 MPa [3,4]. Due to the relatively low PbTe microhardness value a layer of this compound is so soft that it can be scratched easily.…”
Section: Introductionmentioning
confidence: 99%
“…On the other (1251) hand, a modification of the heat transport in this material by high doping or mixing/alloying with a variety of compounds seems to be a hot topic for the last few years. The search for mechanically stable PbTe-based thermoelectric materials by the crystal doping with Sn, I, or Na [4], improved mechanical properties of PbTe containing Ge [5], Na [6] and Ca [7] are just a few examples of papers related to the problem mentioned above. In particular, the properties of (Pb,Cd)Te solid solution formed by PbTe alloying with CdTe -well-known and widely investigated compound of II-VI type -were the subject of several reports in the past.…”
Section: Introductionmentioning
confidence: 99%